2023
DOI: 10.1136/bmjopen-2023-072077
|View full text |Cite
|
Sign up to set email alerts
|

Medical evidence assisting non-fatal strangulation prosecution: a scoping review

Abstract: ObjectivesNon-fatal strangulation (NFS) is a serious form of gendered violence that is fast becoming an offence in many jurisdictions worldwide. However, it often leaves little or no externally visible injuries making prosecution challenging. This review aimed to provide an overview of how health professionals can support the prosecution of criminal charges of NFS as part of regular practice, particularly when externally visible injuries are absent.MethodEleven databases were searched with terms related to NFS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
2
0
0
Order By: Relevance
“…In congruence with previous studies [ 33 ], the number of subjective symptoms reported by the victims did not correlate significantly with the number of MRI findings. This underlines that most symptoms highly depend on the subjective perception of the victim.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In congruence with previous studies [ 33 ], the number of subjective symptoms reported by the victims did not correlate significantly with the number of MRI findings. This underlines that most symptoms highly depend on the subjective perception of the victim.…”
Section: Discussionsupporting
confidence: 90%
“…The most common categories of external injuries in our study, i.e. abrasions, erythema and bruises, corresponded well with literature [33]. However, the number of external findings did not correlate with the number of MRI findings, with more findings found internally than externally.…”
Section: Discussionsupporting
confidence: 89%
“…The experimental model ultimately concluded that the amount of force applied, irrespective of the victim's attempts at self-defense, exceeded 5 kg, and was enough to cause blood vessels in the neck to constrict [10][11][12][13][14]. These findings were presented in Court as scientific evidence that the manner and force of the strangulation were indeed consistent with an attempted murder [15][16].…”
Section: Outcome Of Strangulationmentioning
confidence: 99%